Shaken and Stirred: A Comparative Study of Earthquake‐Triggered Soft‐Sediment Deformation Structures in Lake Sediments - Ariana Molenaar; Katleen Wils; Maarten VanDaele; Christoph Daxer; Nathalie Dubois; Anja Grießer; Patrick Oswald; Arne Ramisch; Michael Strasser; Jasper Moernaut (Geochemistry, Geophysics, Geosystems, 2024)
Abstract Subaqueous paleoseismic studies used soft sediment deformation structures (SSDS) to discern the shaking strength of past earthquakes, as the deformation degree of SSDS related to Kelvin Helmholtz Instability evolves from disturbed lamination and folds to intraclast breccia with higher peak ground accelerations (PGA). We lack comparative studies of different sediment types with SSDS related to earthquakes from different seismogenic sources to comprehend how these factors modulate earthquake‐induced deformation. Here, we compile sediment records with seven earthquake‐triggered SSDS from 10 lakes with organic‐, carbonate‐, siliciclastic‐, and diatom‐rich sediment from three subduction zones and one collisional setting. We target basin sequences with slope angles <0.65° to reduce the influence of gravitational downslope stress. We find that even minimal increases in slope angle, maximal 1°, lead to higher deformation degrees and, for some earthquakes, SSDS are only present at >0.65°. Fine‐grained clastics enhance sediment susceptibility to deformation, whereas abundant diatoms reduce it, demonstrating the influence of composition. Deformation correlates best with PGA and the vicinity of the earthquakes, suggesting that high frequency shaking promotes deformation. In addition, deformation only occurs above a minimum magnitude dependent on sediment composition, and higher deformation degrees in our studied basin sedimentary sequences only above Mw 4.9 for all sediment types, suggesting that sufficient duration of shaking—magnitude correlates with duration—is essential for SSDS development. We advise taking multiple cores on gentle slopes to study SSDS—additional to basin cores—to resolve small magnitude local earthquakes and relative differences in frequency content of past events.